Pre-treatment effect on the structure of bacterial cellulose from Nata de Coco (Acetobacter xylinum) - Rusdi, Rusaini Athirah Ahmad; Halim, Norhana Abdul; Norizan, Mohd Nurazzi; Abidin, Zul Hazrin Zainal; Abdullah, Norli; Che Ros, Fadhlina; Ahmad, Nurazlin; Azmi, Ahmad Farid Mohd (Polimery, 2022)
This paper presents a structural analysis of various methods to produce bacterial cellulose (BC) from Nata de Coco (Acetobacter xyllinum). BC sheet, BC chem and BC mech powder were successfully prepared using oven drying, chemical and mechanical treatment. The X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, and field emission scanning electron microscopy (FESEM) were used to analyze the structure of prepared BC. The structure of bacterial cellulose was compared with the structure of commercial microcrystalline cellulose (MCC) and cotton fabric. The XRD results showed that the BC sheet sample had the highest degree of crystallinity (81.76%) compared to cotton cellulose (75.73%). The crystallite size of cotton was larger than the BC sheet, with the value of 6.83 ηm and 4.55 ηm, respectively. The peaks in the FTIR spectra of all BC were comparable to the commercial MCC and cotton fabrics. FESEM images showed that the prepared BC sheet, BC mech, and BC chem had an almost similar structure like commercial MCC and cotton fabric. It was concluded that simple preparation of BC could be implemented and used for further BC preparation as reinforcement in polymer composites, especially in food packaging.